Prevention, Detection and Response to incidences of substandard and falsified medical products in the Member States of the Southern African Development Community - Stanislav Kniazkov; Sakhile Dube-Mwedzi; Jean-Baptiste Nikiema (Taylor & Francis Group, 2020)
Background Medical products are an integral and pivotal part of health care delivery. They need to be available, affordable and quality-assured. The SADC region is prone to threats arising from the availability and use of substandard and falsified (SF) medical products. This is something that needs to be actively addressed. Method A survey, constructed around four themes, was carried out between September 2018 and January 2019. The National Medicines Regulatory Authorities (NMRAs) of the 16 Member States within the SADC region were asked to respond to the survey questionnaire. The objective was to map existing fameworks, mechanisms and approaches to prevention, detection and response (PDR) to SF medical products. Results Responses were received from twelve out of the sixteen NMRAs. Only three of the twelve respondents had included elements for PDR for SF medical products in their national medicine policies. Regardless of the status in terms of policies, legislation is however in place for the majority of NMRAs. The mandate for regular sampling, an important detection mechanism, was enshrined in the legislation of nine of the twelve respondents. In terms of response mechanisms, six of the respondents had both inter-agency and intra-agency co-ordination for responding to SF products. Conclusion Though findings point to some deficiencies in terms of policies and implementation plans, the majority of countries have the mandate and legislation to deal with substandard and falsified medical products. Effective enforcement requires more investments into human resources, infrastructure, stakeholder coordination and public outreach. WHO has an important source of actionable information about incidience of substandard and falsified medical products. It needs to be leveraged to improve outreach to stakeholders and to raise awareness about SF problem and mechanisms available to address it. The extent, to which mechanisms and procedures are in place, varies. Some elements of the desired approach exist in the region; however, they will benefit from targeted strengthening to ensure a holistic approach across 12 action areas recommended by WHO.